Infectious complications in patients with myelodysplastic syndromes: a review of the literature with emphasis on patients treated with 5-azacitidine - Radsak, Markus Philipp; Hofmann, Wolf-Karsten; Nolte, Florian (European journal of haematology, 2017)
Myelodysplastic Syndromes are oligo-clonal stem cell disorders that are associated with cytopenias in the peripheral blood. Major causes for morbidity and mortality in myelodysplastic syndromes (MDS) patients are infections mostly due to bacteria or fungi. Beside leucopenia per se in affected patients, function of white blood cells particularly that of neutrophils seems to be impaired. Here we summarize the available data on infections in MDS patients in general and particularly those treated with 5-azacitidine.
Gesehen am 12.07.2018
First published: 21 March 2017